Regulatory T cells (Tregs) in lymphoid malignancies and the impact of novel therapies - Maharaj, Kamira; Uriepero, Angimar; Sahakian, Eva; Pinilla-Ibarz, Javier (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) are responsible for maintaining immune homeostasis by controlling immune responses. They can be characterized by concomitant expression of FoxP3, CD25 and inhibitory receptors such as PD-1 and CTLA-4. Tregs are key players in preventing autoimmunity and are dysregulated in cancer, where they facilitate tumor immune escape. B-cell lymphoid malignancies are a group of diseases with heterogenous molecular characteristics and clinical course. Treg levels are increased in patients with B-cell lymphoid malignancies and correlate with clinical outcomes. In this review, we discuss studies investigating Treg immunobiology in B-cell lymphoid malignancies, focusing on clinical correlations, mechanisms of accumulation, phenotype, and function. Overarching trends suggest that Tregs can be induced directly by tumor cells and recruited to the tumor microenvironment where they suppress antitumor immunity to facilitate disease progression. Further, we highlight studies showing that Tregs can be modulated by novel therapeutic agents such as immune checkpoint blockade and targeted therapies. Treg disruption by novel therapeutics may beneficially restore immune competence but has been associated with occurrence of adverse events. Strategies to achieve balance between these two outcomes will be paramount in the future to improve therapeutic efficacy and safety.